Gender Vocabulary in Qs. Al-Hujurat: Lexicological Study - Dyah Ayu Khoirunnisa; Arina Elma Husna; Nur Hasaniyah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to find out the forms of gender vocabulary in Al-Hujurat and the meaning gender vocabulary. This study uses qualitative research, by collecting information in the form vocabulary and analyzing by presenting data to be studied. Al-Hujurat is the primary data source used to find data, as wellas several other supporting books and journals related to theory. The results of gender vocabularyresearchin Al- Hujurat lexicology study are: (1) the forms gender vocabulary in Al-Hujurat consist (a) two forms of مؤنث (female) vocabulary; (b) seven forms of مذكر (male) vocabulary; (c) five forms of gender netral vocabulary; (2) analysis of the meaning of gender vocabulary in Al-Hujurat consisting of (a) the meaning of مؤنث (female) vocabulary; (b) meaning of muzakkar vocabulary (male); (c) meaning of gender netral vocabulary. From several gender vocabularies that the researcher analyzed, such mu'annas, muzakkar, and gender neutral, the researcher found diverse vocabularies. The meaning of gender contained in Al-Hujurat, researchers found various meanings of mu'annas vocabulary including: al-nisa' (adult women) and األنثى (girls). The meanings of muzakkar vocabularyinclude: al-zakar, an-nabi, akhun, al-rosul, and al-mu'minun. The meanings of gender netral vocabulary include: آمنوا, الناس, طائفتين, Allah, and قوم.